Mitigating Mercury Chloride-Induced Spleen Toxicity in Wistar Rats: The Efficacy of Newbouldia laevis Ethanol Extract - Calmday-Ombo D; Innih SO (Ibom Medical Journal)
Background: Mercury chloride toxicity poses significant health risks, particularly affecting organs such as the spleen. Newbouldia laevis is reputed for its medicinal properties, yet its potential to counteract mercury chloride-induced splenic toxicity remains largely unexplored. This study investigated the effects of ethanol extract of N. laevis on mercury chloride-induced spleen toxicity in Wistar rats.